Thermophysiological Comfort Properties of Ripstop Fabrics for Enforcement Personnel Clothing - Zahari, N.; R. Ahmad, M.; F. Yahya, M.; M. Che Muhamed, A.; Yahaya, R. (International Journal of Engineering and Technology, 2018)
The choice of fabric parameters such as fiber type and structure play a key role in the thermoregulatory process as they can determine the change and loss of heat and moisture through sweat evaporation and heat dissipation. In this paper, the thermophysiological comfort properties of ripstop fabrics with different material composition percentages of polyester/cotton (P50C50 and P35C65) and nylon/cotton (N50C50 and N20C80) are reported. The study focuses on the fabricâ€™s air permeability, thermal resistance and water vapour resistance. The results suggest that the air permeability of the fabrics depends on thread density. Fabrics with the lowest thread density (P50C50) have a more open structure and therefore allow more air to pass through it. The results also indicate that the fibre content affects the thermal resistance of the fabrics. Fabrics with lower proportion of cotton, P50C50 and N50C50, show lower thermal resistance results. With regards to water vapour resistance, fabrics containing nylon fibres (N20C80 and N50C50) gave higher resistance in comparisons with fabrics containing polyester (P35C65 and P50C50). The opposite trend was seen with water vapour permeability results. Overall, fabric of P50C50 gave the best thermophysiological comfort properties as indicated from the study.Â Â